Construction of Fiber Optical Communication System Infrastructure for 3T (Terdepan, Terluar dan Tertinggal) Areas Using Fiber to the Area Network System - Pane, Grace Deborah Maria; Rizky, Muhammad Arief; Putri, Crystal Ilesta; Hambali, Akhmad (Global Writing Academica Researching and Publishing, 2023)
Distribution of telecommunications in Indonesia, the government is aggressively building telecommunications network facilities, especially for 3T areas (Frontier, Outermost and Disadvantaged). Because there are still many areas that have not received access to telecommunications services, the Fiber to The Area (FTTA) network is the right solution to meet the needs of the community in economic, environmental and technical aspects. This design will provide an expansion of Fixed Broadband services around the Tanjung Lesung Special Economic Zone (SEZ), Pandeglang Regency, Banten. Later this fiber optic access network will use a Fiber To The Area (FTTA) network topology that connects the CO (Central Office) as a Metro Ethernet and DWDM hub with the Mini OLT Shelter as an Optical Line Terminal (OLT) hub supported by NG-PON (Next-Generation) PON (Passive Optical Network) technology with 2 Stage architecture which involves two stages of sending information signals through optical fiber. This design must first be designed on Google Earth to determine the fiber optic cable path and to determine the feasibility of performance on the system the author uses several test components including: Link Power Budget (LPB) testing, Rise Time Budget (RTB), Signal to Noise Ratio (SNR), Bit Error Rate (BER), Quality Factor (Q-Factor) which is simulated on optisystem to be able to provide performance values that match the eligibility standards at PT Telkom Indonesia.